The Modification of Counsellor Performance Inventory in Malaysian Context - Aqilah, Yusoff; Nor Mazlina, Ghazali; Azzahrah, Anuar; Wan Marzuki, Wan Jaafar; Edris, Aden; Anis Nurshafiqah, Azhar; Sim, Chia Wei (2020)
Research questionnaires are not always translated appropriately before they are used in new temporal, cultural or linguistic settings. Thus, the results based on such instruments may therefore not accurately reflect what they are supposed to measure. Gjersing et al., (2010). Research has shown that there were only a few literatures in counselling supervision that had been investigated, said Wan Marzuki Wan Jaafar (2011). This study aims to modify the Counsellor Performance Inventory (CPI) by Iannelli (2000) into Malaysian context. The original dimensions on CPI cover the following things: Counselling Skills, Counselling Knowledge and Interpersonal Relationship. This research is a research development aims to modify the original inventory into Malaysian context that considerate of the cultural and ethical practices and added a new dimension known as Professionalism and Ethical Practices. This paper was intended to explain the modification process involved in this study according to Stewart et al., (2012) recommended the researcher to include the reports of: 1) Features of the original measure that required modification; 2) Source of information on the basis for modifications; 3) Specific type of modification made; and 4) How the modified measure was tested for psychometric adequacy and results. Additionally, by implemented the modification on the instrument, it will get the gaps closer and measure what it’s supposedly to be measure.